Effect of pharmaceutical promotion and incentives offered by pharmaceutical companies on the prescribing pattern of medical students: a cross-sectional study from a developing nation Pakistan - Gillani, Ali Hassan; Arshad, Hafsa; Umer, Muhammad Farooq; Arshed, Muhammad; Khan, Farman Ullah; Bashir, Kamran; Xu, Sen; Mujtaba, Hasan; Mohamed Ibrahim, Mohamed Izham; Fang, Yu (Frontiers in Medicine, 2024)
Background Pharmaceutical companies continuously pursue healthcare professionals, starting from the medical college level, which can ultimately lead to irrational prescribing of drugs and antibiotics. Therefore, our main aim was to evaluate the opinions and attitudes of medical students toward pharmaceutical promotion. Methods This study utilized a cross-sectional online survey that applied the snowball sampling technique. Data were collected from three public and three private sector medical colleges in Punjab, Pakistan using snowball sampling. A modified version of a pre-structured questionnaire was used to collect data between October 2020 and January 2021. Medical students from the third year onward were captivated. The tool was made available on Google Forms and students could access it by clicking the link shared. The effect of promotion on prescribing pattern and future prescribing of antibiotics were measured. Descriptive statistics, chi-square, and t-test were used to analyze the data. Results A total of 1,301 students filled out the survey, but only 1,227 responses were acceptable. The average age was found to be 23.4 ± 1.59 years. Slightly more than half of the respondents were male participants (57.7%), and a significant proportion (84.1%) reported being aware of pharmaceutical promotion. A smaller number (27.7%) felt that physicians who meet medical representatives more frequently tend to prescribe more antibiotics and 46.3% indicated they would be willing to prescribe antibiotics under the promotional influence. Medical students who were male, in senior college years, attended government institutions, and had lower parental income showed significantly higher perception and attitude scores (p < 0.05) which, in turn, may show their inclination to promotional activities. Many students agreed with the view that pharmaceutical promotion (PP) activities may alter prescribing practices and also believed that they contribute to the increased irrational prescribing of drugs and antibiotics. Conclusion The study revealed that only a small number of students are willing to engage in promotional activities and accept rewards, which influences their choice toward selection of drugs and antibiotics. This study highlighted the necessity of giving proper educational instructions regarding the promotion of drugs to medical students. This study also focused on the educational prerequisites of the students.